2023
DOI: 10.26434/chemrxiv-2023-jqbqt
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Closed-Loop Transfer Enables AI to Yield Chemical Knowledge

Nicholas Angello,
David Friday,
Changhyun Hwang
et al.

Abstract: AI-guided closed-loop experimentation has recently emerged as a promising method to optimize objective functions,1,2 but the substantial potential of this traditionally black-box approach to reveal new scientific knowledge has remained largely untapped. Here, we report a new AI-guided approach, dubbed Closed-Loop Transfer (CLT), that integrates closed-loop experiments with physics-based feature selection and supervised learning to yield new scientific knowledge in parallel with optimization of objective functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 52 publications
(61 reference statements)
0
1
0
Order By: Relevance
“…The work of Angello et al demonstrated an SDL focused on discovering organic optoelectronics with good photostability, particularly for organic photovoltaic (OPV) applications. 643 Like in the previously discussed works on automated organic molecule synthesis, 610,638 the chemical space was predefined through the combination of molecular fragments through iterative Suzuki-Miyaura coupling reactions. 428 In this case, the fragments were acceptor and donor complexes connected by a bridge fragment; this is a common design for OPV applications, with light-induced charge separation encouraged by the difference in local electronic energy levels.…”
Section: Molecules In Solutionmentioning
confidence: 99%
“…The work of Angello et al demonstrated an SDL focused on discovering organic optoelectronics with good photostability, particularly for organic photovoltaic (OPV) applications. 643 Like in the previously discussed works on automated organic molecule synthesis, 610,638 the chemical space was predefined through the combination of molecular fragments through iterative Suzuki-Miyaura coupling reactions. 428 In this case, the fragments were acceptor and donor complexes connected by a bridge fragment; this is a common design for OPV applications, with light-induced charge separation encouraged by the difference in local electronic energy levels.…”
Section: Molecules In Solutionmentioning
confidence: 99%